Rapid evolution of the visual system: a cellular assay of the retina and dorsal lateral geniculate nucleus of the Spanish wildcat and the domestic cat - Williams, RW (J Neurosci, 1993)
The large Spanish wildcat, Felis silvestris tartessia, has retained features of the Pleistocene ancestor of the modern domestic cat, F. catus. To gauge the direction and magnitude of short-term evolutionary change in this lineage, we have compared the retina, the optic nerve, and the dorsal lateral geniculate nucleus (LGN) of Spanish wildcats and their domestic relatives. Retinas of the two species have the same area. However, densities of cone photoreceptors are higher in wildcat-- over 100% higher in the area centralis--whereas rod densities are as high, or higher, in the domestic lineage. Densities of retinal ganglion cells are typically 20–100% higher across the wildcat retina, and the total ganglion cell population is nearly 70% higher than in the domestic cat. These differences are confined to the populations of beta and gamma retinal ganglion cells. In contrast, the population of alpha cells is almost precisely the same in both species. The wildcat LGN is much larger than that of the domestic cat and contains approximately 50% more neurons. However, cell size does not differ appreciably in either the retina or LGN of these species. The differences in total numbers of ganglion cells and LGN neurons correspond neatly to the overall decline in brain size in the domestic lineage and to allometric predictions based on average species differences in body size. We suggest that an increase in the severity of naturally occurring cell death is the most plausible mechanism that can account for the rapid evolutionary reduction in cell populations in this feline lineage.